Potential mechanisms involved in regulating muscle protein turnover after acute exercise: A brief review - Hajj-Boutros, Guy; Karelis, Antony D.; Cefis, Marina; Morais, José A.; Casgrain, Juliette; Gouspillou, Gilles; Sonjak, Vita (Frontiers in Physiology, 2023)
It is well established that resistance training increases muscle mass. Indeed, there is evidence to suggest that a single session of resistance training is associated with an increase in muscle protein synthesis in young adults. However, the fundamental mechanisms that are involved in regulating muscle protein turnover rates after an acute bout of physical exercise are unclear. Therefore, this review will briefly focus on summarizing the potential mechanisms behind the growth of skeletal muscle after physical exercise. We also present mechanistic differences that may exist between young and older individuals during muscle protein synthesis and breakdown after physical exercise. Pathways leading to the activation of AKT/mTOR signals after resistance exercise and the activation of AMPK signaling pathway following a HIIT (High intensity interval training) are discussed.